Evaluation of spin in the abstracts of orthopedic trauma literature: A cross-sectional review. Issue 7 (July 2021) - Shepard, Samuel; Checketts, Jake; Eash, Colin; Austin, Jennifer; Arthur, Wade; Wayant, Cole; Johnson, Mark; Norris, Brent; Vassar, Matt
Abstract: Objectives: A cross-sectional analysis of orthopedic trauma randomized controlled trial (RCT) abstracts to assess the frequency and manifestations of spin, the misrepresentation or distortion of research findings, in orthopedic trauma clinical trials. Methods: The top 5 orthopedic trauma journals were searched from January 1, 2012, to December 31, 2017. RCTs with nonsignificant endpoints ( p > .05) were analyzed for spin in the abstract. The primary endpoint of our investigation was the frequency and type of spin. The secondary endpoint was to assess whether funding source was associated with the presence of spin. Due to the low reporting of funding sources no statistics were able to be computed for this outcome. Results: Our PubMed search yielded 517 articles. Primary screening excluded 303 articles, and full text evaluation excluded an additional 161. Overall, 53 articles were included. Spin was identified in 35 of the 53 (66.0%) abstracts analyzed. Evidence of spin was found in 21 (39.6%) abstract results sections and 22 (41.5%) abstract conclusion sections. Of the 21 RCTs reporting a clinical trial registry, 3 (14.3%) had evidence of selective reporting bias. Conclusions: Orthopedic trauma RCTs from highly ranked journals with nonsignificant endpoints published from 2012 to 2017 frequently have spin in their abstracts. Abstracts with evidence of spin may influence a reader's perception of new drugs or procedures. In orthopedic trauma, the implications of spin may affect the treatment of patients with orthopedic trauma, so efforts to mitigate spin in RCT abstracts must be prioritized.